Electron beam irradiation of carbon black filled linear low-density polyethylene - Ahmad A.; Mohd D.H.J.; Abdullah I. (2023)
A study was conducted on the influence of radiation crosslinking on positive temperature coefficient (PTC) and negative temperature coefficient (NTC) on carbon black filled polyethylene. However, there was no study reported on electron beam irradiation of carbon black filled LLDPE. This paper reports on the influence of radiation crosslinking and carbon black filler loading on the properties of LLDPE with respect to changes in mechanical properties and phase morphology.